Prevention of postpartum hemorrhage in vaginal deliveries. (January 2023) - Angarita, Ana M.; Cochrane, Elizabeth; Bianco, Angela; Berghella, Vincenzo
Abstract: Identification of patients at risk for postpartum hemorrhage (PPH) may allow for prompt diagnosis and intervention. Individual risk factors, risk assessment tools and prediction models have been used for determining a patient's risk of PPH. Measures for the prevention of PPH include identification and management of iron deficiency anemia, unit readiness and preparedness through performing regular simulations and having a PPH cart or medication kit readily available, prophylactic uterotonic - carbetocin alone or dual agents such as oxytocin and misoprostol or oxytocin and methylergometrine or antifibrinolytic (oxytocin and tranexamic acid) use in the third stage of labor immediately after fetal head delivery, and controlled cord traction.